A live attenuated strain of HY9901ΔdctP provides protection against Vibrio alginolyticus to the pearl gentian grouper (♀Epinephelus fuscoguttatus × ♂Epinephelus lanceolatus) - Zhang, Yilin; Zhang, Ziyu; Zhang, Jinxia; Huang, Yucong; Jian, Jichang; Cai, Shuanghu (Frontiers in Marine Science, 2022)
In recent decades, vibriosis caused by Vibrio alginolyticus has become a severe threat to the global mariculture industry. There is an urgent need for an effective vaccine to alleviate this unoptimistic situation. In this study, we evaluated the safety, immunoprotection, and specific and non-specific immune response effect of ΔdctP strain as a live-attenuated vaccine to pearl gentian grouper (♀Epinephelus fuscoguttatus × ♂Epinephelus lanceolatu). The results demonstrate that the safe dose of ΔdctP was ≤1.0 ×106 CFU in pearl gentian grouper. The relative percent survival of the pearl gentian grouper challenged with the ΔdctP mutant strain by intraperitoneal injection reached 74.4%, which was significantly higher than that of the control group. Meanwhile, the expression level of immune-relative genes, including IgM, IL-1β, IL-8, IL-10, MHC-Iα, MHC2, TNF-α, TLR3, and CD4, were upregulated in liver, spleen, and head kidney within 28 d post-vaccination. Moreover, specific antibody IgM, total serum protein as well as activities of catalase, superoxide dismutase, and lysozyme in serum were significantly up-regulated in vaccinated groupers compared with those in control. Collectively, ΔdctP could be used as a live-attenuated vaccine candidate against V. alginolyticus infection in pearl gentian grouper.